Identification, Characterization, and Expression Analysis Reveal Diverse Regulated Roles of Three MAPK Genes in Chlamys farreri Under Heat Stress - Liu, Zhi; Huang, Xiaoting; Yang, Zujing; Peng, Cheng; Yu, Haitao; Cui, Chang; Hu, Yuqing; Wang, Xuefeng; Xing, Qiang; Hu, Jingjie; Bao, Zhenmin (Frontiers in Physiology, 2021)
Mitogen-activated protein kinase (MAPK) cascades are fundamental signal transduction modules in all eukaryotic organisms, participating growth and development, as well as stress response. In the present study, three MAPK genes were successfully identified from the genome of Chlamys farreri, respectively, named CfERK1/2, CfJNK, and Cfp38, and only one copy of ERK, JNK, and p38 were detected. Domain analysis indicated that CfMAPKs possessed the typical domains, including S_TKc, Pkinase, and PKc_like domain. Phylogenetic analysis showed that three CfMAPKs of MAPK subfamilies exists in the common ancestor of vertebrates and invertebrates. All CfMAPKs specifically expressed during larval development and in adult tissues, and the expression level of CfERK1/2 and Cfp38 was apparently higher than that of CfJNK. Under heat stress, the expression of CfERK1/2 and Cfp38 were significantly downregulated and then upregulated in four tissues, while the expression of CfJNK increased in all tissues; these different expression patterns suggested a different molecular mechanism of CfMAPKs for bivalves to adapt to temperature changes. The diversity of CfMAPKs and their specific expression patterns provide valuable information for better understanding of the functions of MAPK cascades in bivalves.